Improving The Students’ Reading Comprehension In Narrative Text By Using Story Pyramid At Eighth Grade Students Of MTs Fathul Huda - Lizatria Paulinsyah; Sri Wahyuni; Yoga Pratama (Jurnal Intelek Dan Cendikiawan Nusantara, 2025)
The aimed of this study was to find out the use of the Story Pyramid strategy could significantly improve students’ reading comprehension in narrative texts. The writer conducted this study at MTs Fathul Huda with the total population was 69 students, by applying purposive sampling that consists of experimental and control group. The writer used a quasi-experimental design and using multiple choice test that consists of 40 items. And the result of the test showed that the t-obtained was higher than t-table (6.447 > 2.014). The Paired Sample t-test results in the experimental class indicated a clear improvement. This improvement was statistically significant across all five aspects of reading, main idea, detail, sequence, inference and vocabulary which means that the used of the Story Pyramid strategy consistently supported the improvement of students’ reading comprehension. In conclusion, Story Pyramid can apply to improve the students’ reading comprehension.